Dyslipidemia and associated factors among diabetic patients attending Durame General Hospital in Southern Nations, Nationalities, and People’s Region - Bekele S (Dove Medical Press, 2017)
Shiferaw Bekele, Tagesech Yohannes, Abdurehman Eshete Mohammed Department of Medical Laboratory Sciences, College of Health Sciences, Jimma University, Jimma, Ethiopia Background: Diabetes mellitus is a group of metabolic disorders that are caused by deficiency in insulin secretion or the decreased ability of insulin to act effectively on target tissues, particularly muscle, liver, and fat. As a result of insulin resistance in the target tissues, particularly in the adipocytes, free fatty acid flux is increased, leading to increased lipid synthesis in hepatocytes, which is responsible for diabetic dyslipidemia.Objective: The objective of this study was to determine the prevalence and associated factors of dyslipidemia among diabetic patients in Durame General Hospital in Kembata Tembaro zone.Methods: A cross-sectional study was conducted from September 2015 to April 2016. In total, 224 subjects were involved in the study by using convenient sampling techniques. Face-to-face interview–administered questionnaire was used to collect sociodemographic data and other possible clinical data associated with the prevalence of dyslipidemia. Fasting venous blood specimens were collected to assess serum lipid profiles. Blood pressure (BP), weight, height, and waist circumference were measured.Results: The prevalence of dyslipidemia was 65.6%. Individual lipid abnormality of elevated LDL-C, TC, TG, and reduced HDL-C were identified in 43.8%, 23.7%, 40.6%, and 41.9% of study subjects, respectively. The prevalence of dyslipidemia was significantly associated with high BP, high body mass index, aging, and longer duration of diabetes mellitus. Conclusion: High prevalence of dyslipidemia was found among diabetic patients in the study area. Therefore, a compressive mechanism is required to screen, treat, and prevent dyslipidemia. Keywords: diabetes, lipid profile, Jimma, Ethiopia